The Effectiveness of Integrated Supply Chain Management In Internal Audit As A Tool For Cost Control - Firas Khudhair Abbas Al Zubaidi; Ali Abdulhussein Raji; Dheyaa zamil khudhair (International Journal of Supply Chain Management, 2019)
In a bid to increase the level of organizational efficiency and success, internal auditors always form an essential part of a firm's supply chain management process. Based on their role of ensuring proper risk reduction through detection and prevention of fraud within organizations, the role of internal auditors cannot be overlooked. The supply chain has major impact on the company's business strategy directly affecting its operational costs. Supply chain performances within the organization have a significant impact on the company's ability to provide services to their customers and create added value. Internal audit of the supply chain is one of the most powerful and fastest ways to reduce operational costs and provide the company competitive advantages in the global market in times of economic crisis. The aim of this paper is to present the key areas of internal audit activities in assessing risk and analyzing the functioning of the supply chain. Ensuring the effectiveness of internal audit work and in the discharge of duties, the independence of such an office always has to be guaranteed. The management of the organization still has to provide support to the internal auditors to ensure that they provide timely and accurate data related to costs. This study, therefore, seeks to provide an overall look into the various aspects through which internal audit work may be used in enhancing the control of the organization's costs. Further, the study will identify the gaps that have led to the failures of the system in detecting and preventing cost-related frauds. The study will provide recommendations for addressing such gaps within the internal audit framework.